1996
DOI: 10.1177/000348949610500906
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Three-Dimensional Reconstruction in Human Cochlear Maps: Measurement of the Lengths of Organ of Corti, Outer Wall, Inner Wall, and Rosenthal's Canal

Abstract: This paper describes the application of computer-aided three-dimensional reconstruction to measurements of the length of the organ of Corti (mean +/- SD, 35.58 +/- 1.41 mm), scala tympani outer wall (40.81 +/- 1.97 mm), scala tympani inner wall (18.29 +/- 1.47 mm), and Rosenthal's canal center (15.98 +/- 1.33 mm) in eight adult male cochleas. The Rosenthal's canal center ranged between 1 3/4 and 2 turns, did not appear to be linearly related to the organ of Corti, and lay near the basal end of the latter. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
126
2
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(152 citation statements)
references
References 17 publications
(3 reference statements)
18
126
2
6
Order By: Relevance
“…This finding is consistent with numerous prior reports indicating a large extent of variation in human cochlear length (Bredberg 1968;Ulehlova et al 1987;Wright et al 1987;Hardy 1968;Kawano et al 1996;Ketten et al 1998: Skinner et al 2002. We did not observe a significant difference between female and male OC length as reported by Sato et al (1991), who found OC lengths of 32.3 T 1.8 mm for females and 37.1 T 1.6 mm for males (total n = 18).…”
Section: Measurements Of Oc Sg and Mw And Implications For CIsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is consistent with numerous prior reports indicating a large extent of variation in human cochlear length (Bredberg 1968;Ulehlova et al 1987;Wright et al 1987;Hardy 1968;Kawano et al 1996;Ketten et al 1998: Skinner et al 2002. We did not observe a significant difference between female and male OC length as reported by Sato et al (1991), who found OC lengths of 32.3 T 1.8 mm for females and 37.1 T 1.6 mm for males (total n = 18).…”
Section: Measurements Of Oc Sg and Mw And Implications For CIsupporting
confidence: 93%
“…Our data showed a significant correlation between total length of OC and SG, which suggests that if OC length is known (e.g., from high-resolution CT images), it can be used to estimate the length of the SG. Kawano et al (1996) reported a longer mean value of 15.98 mm for Rosenthal_s canal in the human cochlea. The cochlear reconstructions in that study were made with a computer-aided 3D technique, and the authors also reported a systematic difference between the 2D and 3D reconstructions, with the larger values obtained with the 3D reconstructions.…”
Section: Measurements Of Oc Sg and Mw And Implications For CImentioning
confidence: 93%
See 1 more Smart Citation
“…However, hair cells are usually absent in implant patients after conventional implant surgery. The remaining neural targets, dendrites and cell bodies in the spiral ganglion, do not have the same relationship to distance along the cochlear partition as hair cells (Kawano et al 1996;Sridhar et al 2006). Thus, the Greenwood frequency-place (or frequency to distance along the cochlea) map is not likely to be appropriate for cochlear implant patients.…”
mentioning
confidence: 99%
“…Furthermore, the auditory-nerve fibers do not maintain the same relationship of frequency map to distance along the electrode array as inner hair cells (Kawano et al 1996;Sridhar et al 2006). It is fortunate, however, that CI users are partially able to adapt to distorted frequency-to-place maps (e.g., Fu and Galvin 2003;Faulkner 2006;Smith and Faulkner 2006).…”
Section: Introductionmentioning
confidence: 99%